Advanced intraoperative imaging: Gold standard in brain and spine surgery?. Issue 1 (13th September 2017) - Raabe, Andreas; Fichtner, Jens; Gralla, Jan
There are several unique features of the concept of advanced intraoperative imaging modalities with CT (computed tomography), MRI (magnet resonance imaging) and DSA (digital substraction angiography) inaugurated in one operating tract. For the first time, there is the opportunity to switch from postoperative to intraoperative imaging – when the surgeon can not only check the result of surgery but improve it – but in general, that is, for all specialties, at least theoretically. Intraoperative imaging is a broad term with many technologies already in routine use today, such as image intensifier, ultrasound, fluorescence technologies, and soon. Using intra-operative CT, MRI, and DSA is not indisputable. Does the benefit justify such immense costs, both in building and in maintenance? To evaluate the clinical benefit and possible drawbacks of these technologies and if there's a substantial benefit for the patients. Also, this is a review of literature to evaluate the evidence and clinical impact of advanced intraoperative imaging in neurosurgery. There is one prospective randomized trial showing that intraoperative MRI increases the extent of resection. In spine surgery, there are several randomized trials showing that pedicle screws are inserted more accurately when image guidance is used. However, there is no RCT comparing navigation with intraoperative CT-updated navigation. Several prospective studies are showing that intraoperative DSA is able to identify vascular remnants or vessel occlusions in case of aneurysm-, arteriovenous malformation-and arteriovenous fistula-surgery. A fair comparison of the benefit of these new technologies must take into consideration that other methods of intraoperative imaging or image guidance already exist. Hence, there are some patients in whom the use of the more advanced technologies makes a personal, individual difference that may affect quality of life and survival. We have to differentiate between (1) the best diagnostic procedure and (2) the term "standard of care." Advanced intraoperative imaging is a gold standard in terms of imaging but not a standard of care.